A Spectroscopic and Nondestructive Analysis Methods for Investigation of Inorganic Pigments in A Cultural Heritage in North of Iran - Faramarz Rostami-Charati; Gholamreza Rahmani; Roya Bahadori; Farah Sadat Madani (Wood Research Journal, 2021)
Many of the historical objects that form our cultural heritage are made of wood. Wooden artefacts, wood painted panels and historic furniture represent a significant part of our cultural heritage. Their preservation over time is a challenging task, and insect infestation still represents a primary cause of loss of cultural heritage artifacts. For this reason in this research, wood pigments that are important in the conservation of historical wooden objects are described. The characterization of very stable pigments from a cultural heritage building named by SAGHATALAR which is located in Mazandaran province, a suburb around of Fridonkenar city in the north of Iran near Caspian Sea (Cochakbishehmahaleh village) was investigated. The result were showed no organic materials was find in the four colors (Blue, Red, Yellow and Green) as samples of this building were detected and taken samples from them for characterization and analysis. The spectroscopic techniques that have been used are Fourier transform infrared spectroscopy (FT-IR), X‐ray fluorescence spectroscopy (XRF), X‐ray emission spectroscopy (XRD), Uv-vis spectroscopy, fluorescence spectroscopy, Raman spectroscopy and Mossbauer spectroscopy.